Strengthening Economy with Criwik’s Local Durian Seedling Cultivation: A Community Services Approach - Arafat, Septrial; Tumanggor, John Andri Efendi; Wahyu Imam Santoso (LP2M INSURI Ponorogo, 2025)
Durian, as a significant cultural and economic asset in Rembang Regency, the project engages a farmers' group to enhance seedling production and promote sustainable agricultural practices. Through a series of workshops and training sessions, participants gain hands-on experience in nursery management, propagation techniques, and organic farming methods. This initiative aims not only to improve the quality and yield of Criwick’s local durian seedlings but also to create economic opportunities within the community. By fostering collaboration and knowledge exchange, the project empowers local farmers to establish nurseries and increase their income potential. Additionally, the initiative emphasizes the importance of preserving traditional cultivation practices to ensure the sustainability of Criwick’s local durian varieties. The project ultimately demonstrates Criwick’s local durian nursery, which consists of seed germination, preparation of nursery media, fertilization, and maintenance. Through these community services, it is expected to provide high-quality Criwick’s local durian seedlings. Criwick’s local durian seedlings can be used by the community for their own needs or sold. Revitalize the local economy, enhance agricultural resilience, and strengthen community ties. By investing in Criwick’s local durian seedling cultivation, this initiative aims to create lasting economic benefits and support the region's cultural heritage.